2013
DOI: 10.1002/bit.24990
|View full text |Cite
|
Sign up to set email alerts
|

N‐glycosylation affects the proper folding, enzymatic characteristics and production of a fungal β‐glucosidase

Abstract: Heterologous expression of ß-glucosidase is one of the approaches to enhance the efficiency of fungal cellulase preparations. It has been reported that N-glycosylation affects the structure framework, function and stability of proteins. In this study, a ß-glucosidase from Aspergillus terreus (GenBank: XP_001216552, BglS) was heterologously expressed in Pichia pastoris and Trichoderma reesei. The four asparagine residues were all linked with high-mannose-type oligosaccharides in P. pastoris, whereas only N224 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
34
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 35 publications
5
34
0
1
Order By: Relevance
“…In T. reesei RutC-30, the expression of endo T was potentially activated by Xyr1, as well as lignocellulose degradation-related genes, when cultured on lignocellulose. Thus, the resulted single GlcNAc on the heterologous expressed TrBglS benefitted from its enzymatic activity and thermostability, compared with PpBglS [69]. After deletion of xyr1 , the upregulation of endo T might be due to starvation of carbon sources, which might be an effort to deglycosylate the glycan coat of the glycoprotein composed of the cell wall, and contribute to further protease degradation [67].…”
Section: Resultsmentioning
confidence: 99%
“…In T. reesei RutC-30, the expression of endo T was potentially activated by Xyr1, as well as lignocellulose degradation-related genes, when cultured on lignocellulose. Thus, the resulted single GlcNAc on the heterologous expressed TrBglS benefitted from its enzymatic activity and thermostability, compared with PpBglS [69]. After deletion of xyr1 , the upregulation of endo T might be due to starvation of carbon sources, which might be an effort to deglycosylate the glycan coat of the glycoprotein composed of the cell wall, and contribute to further protease degradation [67].…”
Section: Resultsmentioning
confidence: 99%
“…The influence of glycosylation inhibitors on secretion and properties of proteins were studied before on insects, mushrooms and уeasts [2,4,[13][14][15]. Tunicamicyn was most often used as an inhibitor of glycosylation.…”
Section: Resultsmentioning
confidence: 99%
“…It is known [1] that carbohydrate component plays a substantial role in formation of quaternary structure of protein; it is responsible for protection from degrading influence of proteolytic enzymes during protein synthesis. The presence of N-glycosylated sites in polypeptide may determine the stability of enzyme and create a possibility for creation of supramolecular structures [2,3]. It is shown [2] that N-bound carbohydrates play an important role in secretion, because they are mainly revealed in extracellular enzymes as a part of linker site of a molecule.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been confirmed that N-glycosylation maintains the stability of proteins via the steric hindrance caused by N-linked glycan avoiding the hydrolysis of protease [10][11][12]. The importance of N-glycosylation in regulating the structure and function of cellulases has been reported, which indicated the unique and diversified role that N-glycosylation played [13][14][15][16].…”
Section: Introductionmentioning
confidence: 89%